Kinetics and Optimization of the Photocatalytic Reduction of Nitrobenzene - Patzsch, Julia; Berg, Benedict; Bloh, Jonathan Z. (Frontiers in Chemistry, 2019)
The photocatalytic reduction of nitrobenzene to aniline in alcoholic solutions appears as an interesting alternative to the classical hydration. However, little is known about the influence of reaction parameters on the kinetics of the reaction which were therefore studied herein. The effects of light intensity, catalyst concentration, initial concentration and temperature were systematically investigated under more than 50 different conditions and accurately described with an appropriate kinetic model. The results show that the efficiency of the reaction is extremely high and apparent quantum yields of up to 142% were observed under optimized conditions. Particularly interesting is the fact high efficiencies were also obtained at high reaction rates of up to 74.3 mM/h. Overall these results demonstrate that heterogeneous photocatalytic reactions can be very efficient and productive at the same time and may therefore present a powerful tool in synthetic organic chemistry.